Developing China’s Ports : How the Gateways to Economic Prosperity Were Revived - Aritua, Bernard; Chiu, Hei; Cheng, Lu; Farrell, Sheila; de Langen, Peter (Washington, DC: World Bank, 2022)
Many countries in Africa and Asia have coastlines that present opportunities for them to become gateways for trade between the hinterlands and global trading routes. However, policy makers struggle to translate this potential into engines of economic development and social transformation. In the past 40 years, China has taken advantage of its strategic geographical location and its status as one of the world’s top manufacturing regions. From a very low position on almost all metrics, today China has become home to more than half of the world’s top 50 ports. The rapid development of China’s ports was critical for the country’s remarkable economic growth. What China achieved can be informative; how and why China revived and modernized its port sector is especially relevant and provides valuable lessons for other countries.